THE ANALYSIS OF LANGUAGE STYLE USED IN “SISTERS COURSE” - Widyaiswara, Tiara; Nurman, Moh.; Khotimah, Anisul (TELL - US JOURNAL, 2022)
This study aims to find out the type of language style that students use to communicate in the "Sisters Course". The research uses the quality descriptive method and theories of Martin Joos and Holmes' theory. The result of this study was that researchers found that all students used five types of language styles, namely frozen style, Formal style, Consultative style, Casual style, and Intimate style. Researcher also found factors that influence language style according to Holmes are social factors, age and gender, ethnicity, and social networks. The majority of students come from Java so they use Javanese as their daily language. Researchers suggest that students can apply language styles according to the type of language style as daily communication, while teachers are expected to be able to apply the appropriate type of language style in the expected context.